Distribution of mesenteric cranial artery in the small intestine of Procyon cancrivorus (Cuvier, 1798) (Mammalia, Procyonidae) - doi: 10.4025/actascibiolsci.v32i2.5839 (Acta Scientiarum. Biological Sciences, 2010)
The mesenteric artery is a high caliber vessel dependent on the abdominal artery, right below the emergence of the vessels destined for the liver and stomach. The present study aimed to describe the behavior of the arterial vessel in the small intestine of the crab-eating raccoon (Procyon cancrivorus). The animals were collected on highways (roadkill). Cannulation of the abdominal aorta, perfusion with warmed water (40°C) and stained latex injection (Neoprene 450, Dupont do Brasil and Sulvinil stain, Glassuret S.A) were performed, followed by formaldehyde fixation (10%). The dissection and photographic documents (Sony Cyber-shot, 8.1 megapixels) made it possible to systemize the arteries and define the vascular patterns of the viscera. It was verified that the mesenteric cranial artery supports the entire jejune and the mesenteric portion of the ileum. Next to the mesenteric border, it becomes an anastomosis forming vascular arches from where straight arteries leave, supplying the mesenteric portion and sometimes also the jejunal anti-mesenteric portion. The artery that irrigates the ileum comes up as a branch of the cranial mesenteric artery. Anatomic knowledge of the vascular pattern of the crab-eating raccoon (Procyon cancrivorus) is of fundamental importance for researches regarding the arterial distribution of the intestine considering anatomic variances.